Developing Exchange-Correlation and Kinetic Energy Functional Approximations for Density Functional Theory - Levämäki, Henrik (fi=Turun yliopisto|en=University of Turku|, 2018)
A nearly endless amount of technology relies on the understanding of the properties of matter and materials. Because the properties emerge from the motion of the electrons within matter, deepest and most accurate understanding can only be achieved by measuring or simulating the electronic structure. This thesis considers the computational simulation aspect, and currently the most popular way of conducting these simulations on a computer is density functional theory (DFT). The accuracy of the DFT calculations mostly depends on a small, but very important, component of the total energy — the exchange-correlation (XC) energy. The exact form of the XC energy term is not known and therefore always has to be approximated. When calculating very big systems also the kinetic energy term has to approximated in an orbital-free manner, because computing the electronic orbitals is too expensive for the big systems. Firstly, a new gradient-level XC approximation calledQNAis presented, and it is designed for the calculation of metallic bulk alloys. QNA exploits the subsystem functional scheme to address the issue of inconsistent performance that current gradient-level approximations have with many alloys. QNA is shown to produce more accurate binary alloy formation energies, and the good accuracy of formation energies is very important in alloy theory. Secondly, a new method of computing the kinetic energy without orbitals is presented and tested in practice. This method allows one, in principle, to perform orbital-free calculations for spherically symmetric systems at the high accuracy level of orbital DFT. A succesful orbital-free solution for the electronic structure of the Be atom is presented. One of the ultimate goals in DFT research is to combine the high accuracy of orbital DFT with the excellent computational speed of orbital-free DFT, and the proofof-concept solution for the Be atom is a step in this direction.

Tiheysfunktionaaliteoriaa varten kehitetyt vaihtokorrelaatio- ja liike-energia –approksimaatiot Lähes lukematon määrä teknologiaa nojautuu aineen ja materiaalien ominaisuuksien ymmärtämiseen. Koska nämä ominaisuudet kumpuavat aineen koossapitävästä elektronirakenteesta, syvällisin ja kaikista tarkin ymmärrys voidaan saavuttaa ainoastaan mittaamalla tai simuloimalla kyseistä elektronirakennetta. Tämä väitöskirja käsittelee jälkimmäistä vaihtoehtoa, eli elektronirakenteen mallintamista tietokoneella tehtävien laskujen avulla. Nykyään suosituin tällaisista laskentamenetelmistä on tiheysfunktionaalimenetelmä. Tiheysfunktionaaliteoriaan pohjautuvien laskujen tarkkuus riippuu pääasiassa yhdestä pienestä, mutta erittäin tärkeästä kokonaisenergian komponentista—vaihto-korrelaatioenergiasta. Vaihto-korrelaatioenergian tarkkaa matemaattista muotoa ei tunneta, joten sille on aina käytettävä jotakin approksimaatiota. Kun halutaan mallintaa erittäin kookkaita systeemejä, myös liike-energia on approksimoitava orbitaalivapaalla tavalla, sillä orbitaalien laskeminen kookkaille systeemeille on liian aikaavievää. Ensimmäiseksi tässä tutkielmassa esitetään uusi gradientti-tason vaihto- korrelaatioapproksimaatio QNA, joka on suunniteltu metalliseosten laskemiseen.QNA hyödyntää alisysteemifunktionaaleja (subsystem functional scheme) parantamaan laskujen tarkkuutta metalliseoksille verrattuna nykyisiin gradienttitason funktionaaleihin. Nykyiset gradienttitason funktionaalit eivät useinkaan pysty mallintamaan kaikkia seoksen komponentteja (puhtaat alkuaineet) tarkasti, minkä tässä väitöskirjassa osoitetaan johtavan epätarkkoihin tuloksiin itse seokselle. QNA-approksimaatiossa kukin seoksen komponentti mallinnetaan erillisen alisysteemifunktionaalin avulla, jolloin kukin komponentti ja itse seos voidaan laskea tarkasti. Käytännön laskuilla osoitetaan, että QNA tuottaa erittäin tarkkoja muodostumisenergioita kaksikomponenttisille metalliseoksille, mikä on erittäin tärkeä seikka metalliseosten teoriassa.